Globalization in Africa : perspectives on development, security, and the environment - Tar, Usman A.; Mijah, Etham; Tedheke, Moses E. U. (Lexington Books, 2016)
This book critically examines the impact of globalization on development, security, and the environment in Africa. It assesses multiple fronts of crises unleashed by globalization: development and governance, peace and security, and environment and sustainability. This edited volume also identifies and discusses the challenges and opportunities that globalization poses to African states and societies.